Optimization of Black Tea Drying Temperature in an Endless Chain Pressure (ECP) Dryer - Abhiram, G.; Diraj, R.; Eeswaran, R. (MDPI, 2023)
Drying is a crucial and energy-consuming process in black tea manufacturing that is aimed at reducing moisture content and terminating enzymatic reactions in tea leaves. In Sri Lanka, an endless chain pressure (ECP) dryer is commonly used for drying, but it consumes a significant amount of energy, necessitating the optimization of drying conditions. The current drying temperature at the Houpe tea factory in Ratnapura, Sri Lanka is 121 ◦C (250 ◦F), and it has not been optimized for a considerable period. As a result, energy consumption and wastage are high, leading to an inferior quality of black tea. To optimize factory conditions, tea leaves were dried under different temperatures: 115 (T1), 118 (T2), 121 (T3), 124 (T4), and 127 (T5) ◦C. Energy consumption, energy wastage, and specific energy consumption (SEC) for tea drying were calculated. Additionally, chemical and sensory analyses of samples of made tea were performed. SEC and energy wastage were significantly (p < 0.05) lower for treatments T1 and T2 than for other treatments. The theaflavin and thearubigin contents were significantly (p < 0.05) higher while total phenolic content was moderate for treatment T2. The sensory parameters of T2 outperformed other treatments. Based on these results, the optimum drying temperature for the ECP dryer was determined to be 118 ◦C and this temperature has been recommended for this factory
Keywords: ECP dryer; Energy consumption; Organoleptic properties; Theaflavins; Thearubigins